Making it against the odds: How individual and parental co‐agency predict educational mobility. (23rd April 2021) - Schoon, Ingrid; Burger, Kaspar; Cook, Rose
ABSTRACT: Introduction: This study examines the role of individual agency and parental co‐agency as resource factors enabling educational mobility (university enrolment and degree completion) among first‐generation students. Methods: The study is based on Next Steps, a nationally representative cohort of UK students. Path models were run, linking different dimensions of agency assessed at age 13/14 to educational attainment by age 25/26, controlling for academic attainment and socio‐demographic factors. Results: Educational mobility was predicted by student's expectation to go to university, their expectation of success, and school engagement during secondary school. In addition, parental co‐agency played a significant role ‐ highlighting the importance of parents in supporting upward educational mobility of their children. Conclusions: Multiple dimensions of agency are necessary for disadvantaged students to achieve academically. To support first‐generation students, schools need to provide opportunities for them to become engaged in education, to experience mastery and to develop realistic expectations of success.